Analisis Faktor-Faktor yang Mempengaruhi Efektivitas Pengelolaan Barang Milik Daerah: (Studi pada Badan Pengelola Keuangan dan Aset Kabupaten Malang) - Amerieska, Siti; Setiati, Fita; Mulyono, Imam (LP2M Institut Teknologi dan Bisnis Asia Malang, 2018)
This study aims to analyze the factors of management of regional property. This research was conducted by using quantitative descriptive method. The research method used is associative in which the research aims to determine the relationship between two or more variables. The analysis technique used is factor analysis. Based on the results of the data analysis test, it was found that testing of 33 factors in asset management in the local government environment. The sample uses 50 respondents, data analysis techniques using factor analysis in this research data are grouped into 6 (six) factors, namely: BMD Planning and Procurement (20.71%), Usage and Utilization (18.12%), Security and Maintenance (10 , 05%), Elimination (6.29%), Administration of BMD (5.00%) and Control and Control (4.89%). The results of this study indicate that of the six factors the most dominant factors are the factors of procurement BMD and BMD uses, in fact this is reasonable because planning is very important to be done to support the control and supervision process. While the use and utilization can be said to be effective if supported also by good administration and periodic maintenance.